2013
DOI: 10.5371/hp.2013.25.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Hemiarthroplasty Using Calcar Replacement Stem for Unstable Intertrochanteric Femoral Fracture in Elderly Patients

Abstract: Purpose: The purpose of this study is to evaluate the results of bipolar hemiarthroplasty using calcar replacement stem for comminuted intertrochanteric fracture in elderly patients. Materials and Methods: Between March 1998 and March 2008, the clinical records of 79 cases who were older than 75 years of age and underwent bipolar hemiarthroplaty, using calcar replacement stem with figure of eight and cerclage wiring, were reviewed. Their mean age was 82.4 years(75-92 years) and the mean follow-up period was 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Intertrochanteric femoral fractures are very commonly observed, account for approximately half of all hip fractures 12) , and result in loss of independent living skills, as well as incomplete recovery of physical ability in approximately 50% of cases 13 , 14 , 15) . Several treatment options, such as compression hip screws, metal plates, and intramedullary nails are available, while replacement arthroplasty is performed only in limited cases 3 , 4 , 5 , 6) . These approaches represent various advantages and disadvantages, and therefore, a number of studies regarding their clinical outcomes have been reported 13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intertrochanteric femoral fractures are very commonly observed, account for approximately half of all hip fractures 12) , and result in loss of independent living skills, as well as incomplete recovery of physical ability in approximately 50% of cases 13 , 14 , 15) . Several treatment options, such as compression hip screws, metal plates, and intramedullary nails are available, while replacement arthroplasty is performed only in limited cases 3 , 4 , 5 , 6) . These approaches represent various advantages and disadvantages, and therefore, a number of studies regarding their clinical outcomes have been reported 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Compression hip screws have been widely utilized as treatments for intertrochanteric fractures; however, high fixation failure rates have been reported when they have been used to treat unstable fractures 1 , 2) . Therefore, intramedullary nailing has become a commonly used treatment option in recently years, while replacement arthroplasty has become increasingly reserved for limited cases 3 , 4 , 5 , 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Nam et al9) have reported satisfactory results with cementless total hip arthroplasty and double tension band wiring in fixation of unstable intertrochanteric fractures with the greater trochanteric fragment. Moreover, Cho et al10) and Kho et al11) documented satisfactory results with hip hemiarthroplasty and cerclage wiring in fixation of unstable intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%